Accelerating Educational Technology Adoption in Elementary Schools: The Role of Student Interns as Catalysts for Teacher Acceptance - Yohannes Marryono Jamun; Zephisius Rudiyanto Eso Ntelok; Rikardus Jundu (LP. Ma'arif Janggan Magetan, 2026)
Digital transformation in education requires teachers to integrate technology effectively into teaching and learning processes. However, teachers’ acceptance of educational technology remains uneven and is influenced not only by cognitive perceptions but also by professional interaction in school settings. This study examines the influence of academic interaction between student interns and elementary school teachers on teachers’ attitudes toward adopting learning technology by using the Technology Acceptance Model (TAM). This study employed a quantitative correlational design involving 108 elementary school teachers from partner schools of the Primary School Teacher Education Program at Universitas Katolik Indonesia Santu Paulus Ruteng in East Manggarai Regency. The data were analyzed using Structural Equation Modeling (SEM). The findings show that academic interaction has a positive and significant effect on perceived ease of use and perceived usefulness of technology. Perceived ease of use also positively affects perceived usefulness and teachers’ attitudes toward technology, while attitude toward technology significantly strengthens behavioral intention to use technology in teaching practice. Mediation analysis further indicates that perceived ease of use and perceived usefulness significantly mediate the relationship between academic interaction and teachers’ attitudes toward technology. These findings suggest that academic interaction between student interns and teachers can function as a contextual learning mechanism that accelerates educational technology adoption in elementary schools.